2021
DOI: 10.3389/frcmn.2021.724772
|View full text |Cite
|
Sign up to set email alerts
|

5G New Radio Requires the Best Possible Risk Assessment Studies: Perspective and Recommended Guidelines

Abstract: The development and establishment of mobile communication technologies has necessitated assessments of possible risks to human health from exposures to radio-frequency electromagnetic fields (RF EMF). A number of expert committees have concluded that there is no evidence for such risks as long as exposures are at or below levels that do not allow tissue heating. These assessments have been based primarily on studies investigating frequencies up to 6 GHz including frequencies similar to those used by two of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The introduction of this new technology which operates in different frequency bands has attracted a significant amount of toxicity studies [3][4][5]. To date, however, only a few studies have been conducted on the high frequencies that will be used by 5G [2], and the data are not sufficient to conclude on the existence or not of health effects related to exposure to electromagnetic fields at frequencies around 26 GHz [6].…”
Section: The Impact Of 5g Technology To Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of this new technology which operates in different frequency bands has attracted a significant amount of toxicity studies [3][4][5]. To date, however, only a few studies have been conducted on the high frequencies that will be used by 5G [2], and the data are not sufficient to conclude on the existence or not of health effects related to exposure to electromagnetic fields at frequencies around 26 GHz [6].…”
Section: The Impact Of 5g Technology To Healthmentioning
confidence: 99%
“…Some evidence suggests that the global environment conditions are rapidly changing, and the contaminated conditions could interfere with reproductive mechanisms. In this view, some literature studies have shown biological effects on reproductivity at different frequency bands below 6 GHz [2,5]; thus, in this paper we have investigated the effect of electromagnetic fields at 27 GHz on the sperm quality of bivalve mollusk Mytilus galloprovincialis by in vitro assays. The experiments were conducted with a commercial pyramidal horn antenna with an incident density power not exceeding the international limits set by the ICNIRP for frequencies above 6 GHz; spermatozoa were exposed to electromagnetic fields for up to 1 h, and during the exposure we evaluated motility and vitality, important parameters that reflect the health status of the spermatozoa and consequently the reproductive success of species.…”
Section: The Impact Of 5g Technology To Marine Coastal Marine Speciesmentioning
confidence: 99%
“…But data on damage threshold levels is sparse, and using rate-process models for estimating damage requires verification. To address these gaps in the upper GHz band, others have asked for empirical studies to help inform model development (Foster & Vijayalaxmi 2021, Hirata et al 2021, Mattsson et al 2021. This study attempts to help address both of those concerns by providing thermal responses and histological assessments of 352 trials on swine skin.…”
Section: Introductionmentioning
confidence: 99%
“…As the field of research progresses, exposure guidelines may be adjusted to account for new scientific findings and further understand the potential effects of RF EMF on human health [14]. The development of the NextGEM Innovation and Knowledge Hub for EMF and Health [15] established, starting in 2022, a partnership spanning telecommunication engineering, cell biology, human studies, and epidemiology, and the gained knowledge will be integrated into an evidence-based risk assessment for use by different stakeholders.…”
Section: Introductionmentioning
confidence: 99%